Sediment transport capacity response to variations in water discharge in pressurized subglacial channels - I. Delaney; A. J. Tedstone; A. J. Tedstone; M. A. Werder; M. A. Werder; D. Farinotti; D. Farinotti (The Cryosphere)
Sediment transport capacity in both subaerial and subglacial channels depends on the shear stress exerted across the channel bottom, which varies with water velocity and channel width. In fully subaerial channels, water discharge variations are accommodated by flow depth and width changes along with water velocity. However, in subglacial channels, water is pressurized by the ice above, and they grow in response to the frictional heating of the water flowing through them. As a result, rapid changes in water discharge mainly result in velocity variations, as the channel geometry evolves slowly. Here, we present formulations of sediment transport capacity in different channel types and apply subglacial and subaerial hydraulics models to hydrographs from an Alpine glacier and a catchment of the Greenland Ice Sheet. Numerical experiments show that changing channel size results in sediment transport capacity peaking before the maximum water discharge. This hysteresis causes a highly variable relationship between sediment and water discharge in a transport-limited subglacial system. The results also indicate that high subglacial sediment transport capacities can occur across a wide range of water discharges. Reducing water discharge variability by smoothing lessens the hysteresis effects, in some cases to the point where a covarying relationship between water discharge and sediment transport capacity can be approached, similar to subaerial systems. A second set of numerical experiments shows that subglacial sediment transport is highly non-linear with respect to water discharge, creating more variability in sediment transport capacity. Yet, the results and formulations of subglacial sediment transport capacity show that its variability can approach that of subaerial systems when subglacial channel size is in equilibrium with water discharge. The implications of these findings help to evaluate sediment discharge from glaciers with different hydro-climatic forcings and to establish sources of variability in sediment export–water discharge relationships. These findings can improve the interpretation of sediment discharge records in glacierized catchments.